2020
DOI: 10.1038/s41398-020-0812-z
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal glutamate and hippocampus subfield volumes in antipsychotic-naive first episode psychosis subjects and relationships to duration of untreated psychosis

Abstract: Evidence points toward a relationship between longer duration of untreated psychosis (DUP) and worse long-term outcomes in patients with first episode psychosis (FEP), but the underlying neurobiology remains poorly understood. Proton magnetic resonance spectroscopy studies have reported altered hippocampus glutamatergic neurotransmission, and structural MRI as reported hippocampal atrophy that may be associated with memory impairment in schizophrenia. Here, we quantify left hippocampus glutamate (Glx) and left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 74 publications
3
34
0
Order By: Relevance
“…Our finding is in agreement with a later study that reported a negative relationship between glutamate excess and brain volumes in the caudate nucleus in first episode psychosis patients (91). In contrast, we did not observe a linear relationship between hippocampus subfield volumes and glutamate levels in antipsychotic medication-naïve first episode psychosis patients (69). Interestingly though, those with a longer duration of untreated psychosis showed lower hippocampus subfield volumes.…”
Section: Can Multimodal Brain Imaging Help Us Better Characterize Thesupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding is in agreement with a later study that reported a negative relationship between glutamate excess and brain volumes in the caudate nucleus in first episode psychosis patients (91). In contrast, we did not observe a linear relationship between hippocampus subfield volumes and glutamate levels in antipsychotic medication-naïve first episode psychosis patients (69). Interestingly though, those with a longer duration of untreated psychosis showed lower hippocampus subfield volumes.…”
Section: Can Multimodal Brain Imaging Help Us Better Characterize Thesupporting
confidence: 92%
“…In magnetic resonance spectroscopy studies, we found elevated choline and a disruption of the relationship between NAA and glutamate in the left striatum, indicating possible mitochondrial, membrane, and glial dysfunction ( 72 ). However, we reported no neurometabolite abnormalities in the medial prefrontal cortex or the hippocampus when contrasting antipsychotic medication-naïve first episode patients and controls in the overall group ( 31 , 69 ). It is important to note that glutamate levels in both areas showed a greater variance in patients compared to controls, suggesting heterogeneity in glutamatergic metabolism in first episode psychosis.…”
Section: Key Scientific Questions In Neuroimaging Research In Schizopmentioning
confidence: 60%
See 2 more Smart Citations
“…In this context, it is important to note that the ventral subiculum (VSub), which is part of the hippocampal formation allowing the output of the signals from the CA1 region of the hippocampus, seems to be particularly sensitive to neurodevelopmental alterations in schizophrenia (Rioux et al, 2003; Moyer et al, 2015). Moreover, a reduction in the volume of the left VSub volume was observed in patients with first episode psychosis (Briend et al, 2020). In other respects regarding this conceptual framework, it is worth mentioning that anatomical projections from the VSub towards the shell subregion have been described, as well as NMDA-type glutamatergic receptors present at the presynaptic level on the DAergic terminals in this part of the Nacc (Meredith and Totterdell, 1999).…”
Section: Introductionmentioning
confidence: 99%